Listeria monocytogenes AND INDICATOR MICROORGANISMS IN COALHO CHEESE SOLD IN FAIRS AND SUPERMARKETS IN THE INTERIOR OF PARAÍBA. (REMUNOM, 2025)
Coalho cheese is a traditional and popular dairy product in the Brazilian Northeast and has great socioeconomic relevance. However, its commercialization in street markets and supermarkets may present microbiological risks due to poor storage conditions, compromising food safety. This study aimed to evaluate the presence of Listeria monocytogenes and hygiene indicator microorganisms (mesophilic aerobes, psychrotrophic microorganisms, molds and yeasts) in coalho cheeses sold in street markets and supermarkets in Campina Grande-PB. Twelve cheese samples were collected, half from street markets and half from supermarkets in the city and its districts. The samples were sent to the microbiology laboratory of the Instituto Federal da Paraíba, where the analyses for each microorganism were performed. The results were compared by Student's t-test. The curd cheeses presented high counts of microorganisms indicating hygienic and sanitary quality ranging from 1.1x104 to 3x10⁶; however, there were no significant differences, indicating that in both types of marketing environments, more hygiene and application of good product conservation practices are necessary. The psychrotrophic bacteria indicating storage reiterate the need for better practices to keep the product fit for consumption until the time of purchase; only one sample presented low counts (2x102). Two samples of cheese from the street market were identified with the presence of Listeria in quantities greater than those permitted by Brazilian legislation; these samples are not fit for consumption due to the risk of listeriosis. Keywords: psychrotrophs; molds and yeasts; mesophilic aerobes.